Wicked charms - Evanovich, Janet; Sutton, Phoef (New York : Bantam Books, 2015)
Dazzling her patrons with scrumptious cupcakes at her Salem, Massachusetts, bakery, Elizabeth Tucker continues to fall for the irresistible Diesel, who protects her from a villain who is seeking mystical stones tied to the seven deadly sins.
Keywords: Bakers -- Fiction; Talismans -- Fiction; Marblehead (Mass.) -- Fiction; Mystery fiction